(untitled) (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2022)
Presently there is a rising demand for novel and potent anti-inflammatory drugs of plant origin owing to the lesser amount of side effects compared to Non-Steroidal anti-inflammatory Drugs. On the other hand, microbial resistance to conventional antimicrobial agents has increased during the last three decades. This study aims to overcome these challenges by investigating an herbal plant application.It was designed to evaluate in vitro anti-inflammatory and antibacterial activity of methanolic extracts of leaves, roots and combination of both leaves and roots extracts of Magnolia figo; a native Chinese medicinal plant.In vitro anti-inflammatory property was determined using heat-induced protein (egg albumin) denaturation test using diclofenac sodium as the positive control. Antibacterial activity of the methanolic extract was evaluated against Escherichia coli (ATCC® 25922TM) and Staphylococcus aureus (ATCC® 25923TM) using the cylinder plate method.As a result, considerable dose-dependent anti-inflammatory activities were detected in the combination extract (IC50 =1.819 ug/mL) when compared to the positive control (diclofenac sodium) (IC50 =4.337 ug/mL). Among the extracts, the highest effect against E. coli was exhibited by the combination extract (diameter of inhibitory zone =15.30 mm). None of the extracts showed a positive antibacterial effect against S.aureus. Phytochemical investigations of extracts indicated the presence of alkaloids, flavonoids, phenols, tannins, saponins, terpenoids, glycosides and steroids.This was concluded a significant result elicited by the combination of plant parts confirm that M. figo is a medicinal plant that can be used to develop novel anti-inflammatory and antibacterial agents. Keywords: Anti-inflammatory, Antibacterial, Phytochemical analysis, Magnolia figo, Escherichia coli, Staphylococcus aureus